The effect of light irradiation on a nitro-ruthenium porphyrin complex in the induced death of lung cancer cells in two- and three-dimensional cultures: Insights into the effect of nitric oxide - Becceneri, Amanda Blanque; Martin, Matheus Torelli; Graminha, Angelica Ellen [UNESP]; Cominetti, Márcia Regina; Ford, Peter C.; Santana da Silva, Roberto (Royal Society of Chemistry (RSC), 2024)
Efforts to find compounds selectively affecting cancer cells while sparing normal ones have continued to grow. Nitric oxide (NO) is critical in physiology and pathology, including cancer. It influences cellular processes like proliferation, apoptosis, and angiogenesis. The intricate interaction of NO with cancer cells offers innovative treatment possibilities, but its effects can vary by concentration and site. Ruthenium complexes capable of releasing NO upon stimulation show for this purpose. These versatile compounds can also enhance photodynamic therapy (PDT), a light-activated approach, which induces cellular damage. Ruthenium-based photosensitizers (PSs), delivering NO and producing reactive oxygen species (ROS), offer a novel strategy for improved cancer treatments. In this study, a nitro-ruthenium porphyrin conjugate: {TPyP[Ru(NO2)(bpy)2]4}(PF6)4, designated RuNO2TPyP, which releases NO upon irradiation, was investigated for its effects on lung cells (non-tumor MRC-5 and tumor A549) in 2D and 3D cell cultures. The findings suggest that this complex has potential for PDT treatment in lung cancer, as it exhibits photocytotoxicity at low concentrations without causing cytotoxicity to normal lung cells. Moreover, treatment of cells with RuNO2TPyP followed by light irradiation (4 J cm−2) can induce apoptosis, generate ROS, promote intracellular NO formation, and has anti-migratory effects. Additionally, the complex can modify tumor cell structures and induce photocytotoxicity and apoptosis in a 3D culture. These outcomes are attributed to the internalization of the complex and its subsequent activation upon light irradiation, resulting in NO release and singlet oxygen production.